Functioning of family nursing in transition: an example of a small town in Poland. Are there any benefits for patients? - Marcinowicz, Ludmiła (Health Expect, 2004)
Objective  To evaluate whether organizational changes in the Polish health care system affected patients’ opinions about selected aspects of the quality of care provided by family nurses. Design  Two independent surveys conducted in 1998 and 2002 using face‐to‐face interviews with structured questionnaires. Setting and participants  The study was performed in a small town in Poland, where family physicians were introduced in 1995. The study groups consisted of two samples of patients randomly selected from those registered on the patient list. Altogether 1000 interviews were obtained in survey I (in 1998) and 1000 from another sample in survey II (in 2002). In 1998, family nurses were employed by family physicians, but in 2002 they had established their own practices and held direct contracts with the National Health Fund. Results  The surveys carried out at a 4‐year interval showed a significant increase in the percentage of patients reporting home visits by family nurses, both at the request of physicians and on the nurses’ own initiative (from 16.3 to 45.8%, P < 0.05). Comparative analysis showed that in survey II the percentage of the respondents who were satisfied with nursing care increased from 35.8 to 53.6% (P < 0.05). Conclusion  Care provided by independent nurses was available to a larger group of patients. Patients were more satisfied with the services of family nurses working as independent contractors. The investigations in the present study should be supplemented by a qualitative study.